New world orders in contemporary children's literature: utopian transformations (Palgrave Macmillan, 2011)
This book demonstrates how contemporary children's texts draw on utopian and dystopian tropes in their projections of possible futures. The authors explore the ways in which children's texts respond to social change and global politics. The book argues that children's texts are crucially implicated in shaping the values of their readers.